When life-threatening conditions appear clinically silent: an atypical presentation of spontaneous coronary artery dissection in a 60-year-old female - Yenal Harper; Manyoo Agarwal; Krishna Gannamraj; Sneha Parmar; Inyong Hwang; Shadwan Alsafwah (Greater Baltimore Medical Center, 2016)
Spontaneous coronary artery dissection is a poorly understood phenomenon that usually affects women during pregnancy or the immediate post-partum period. We present the case of a 60-year-old female with chronic obstructive pulmonary disease who presented with vague complaints of shortness of breath, dizziness, and weakness with a mildly elevated troponin. She denied any anginal symptoms. As part of her initial workup, a nuclear stress test revealed inferior wall reversible changes. Coronary angiography revealed spontaneous right coronary artery dissection which was treated with a drug-eluting stent.